Efficacy of Repetitive Transcranial Magnetic Stimulation (r-TMS) Therapy on Improving Motor Strength in Stroke Patients at Dr. Moewardi Surakarta - Ari Revianto; Yetty Hambarsari (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2024)
Background: Stroke, an acute neurological dysfunction, poses a health challenge with a potential fatality, emerging as a leading cause of long-term disability. This study explores the efficacy of repetitive transcranial magnetic stimulation (r-TMS) with medical rehabilitation in enhancing stroke patients' motor strength, comparing it with standard therapy and focusing on the Medical Research Council score. Objective: Stroke is an acute manifestation resulting from neurological dysfunction, persisting for ≥24 hours or leading to death due to blood vessel disorders. The study aims to determine the effectiveness of r-TMS therapy in improving stroke patients' motor strength, comparing it with standard therapy based on the Medical Research Council score. Methods: A quasi-experimental study with a pre-post control group design involved 30 respondents selected through consecutive sampling in stroke units and outpatient clinics. Upper extremity muscle strength, measured with the Medical Research Council score, was analyzed using the Mann-Whitney U test, with a significance level set at p < 0.05. Results: The post-test ranking value of the r-TMS group (20.56) exceeded that of the Non r-TMS group (10.46). The Mann-Whitney U test indicated a significant difference in the average ranking of the Medical Research Council scores between the two groups (p < 0.05, 0.001), highlighting the efficacy of r-TMS therapy in enhancing motor strength. Conclusion: This study shows that stroke patients receiving standard therapy and transcranial magnetic stimulation exhibit improvements in extremity motor strength compared to those undergoing medical rehabilitation alone. The r-TMS group notably showed a significant increase in extremity motor strength.